(untitled) (Teresa Vigetti: Revista de Trabajo Social, 2025)
The present article aims to problematize the sense of written records in Social Work in light of the exponential era we live in. In a context where drones and robots can observe and record data on a scale incomparable to human abilities, and where artificial intelligence algorithms are capable of writing texts in milliseconds, the central question of this work arises: What is the value of written records, even today, for the discipline? In search of possible answers, it is argued that, far from being an anachronistic practice, the written record is reaffirmed as an indispensable instrument for Social Work. Unlike massive data, the record has a unique political and reflective character, capable of capturing singular realities and making visible the lives that, otherwise, could be overshadowed by the vertiginous advance of technology.